MELUKISKAN AKUNTANSI DENGAN KUAS INTERPRETIF - Nurhayati, Nurhayati (Universitas Islam Negeri Sunan Kudus, 2015)
This study departs from the domination of accounting studies using the paradigm of positivistic methodology. The aim in this studyprovides an alternative approach in developing interpretive accounting research. Triyuwono (2013) says there are five paradigms in the social sciences: positivism, interpretivism, criticism postmodernism, and spiritualists. Interpretivis paradigm, critical, postmodernist and spiritualists using qualitative methods, which is the development of positivistic paradigm. This paradigm is not mutually exclusive, ideally an accounting researchers must be able to accept this paradigm, called“multiparadigma” (Triyuwono, 2013). Interpretive considers that truth, reality or real life does not have a one-sided, but it has many facets, can be examined from various viewpoints. Design research in interpretive research, phenomenology, ethnography, ethnometodology, narrative, case studies, and grounded theory.